The Influence of RuO2 Distribution and Dispersion on the Reactivity of RuO2−SnO2 Composite Oxide Catalysts Probed by CO Oxidation. Issue 10 (29th April 2019) - Xu, Xianglan; Liu, Fuyan; Huang, Jin; Luo, Wenping; Yu, Jing; Fang, Xiuzhong; Lebedeva, Olga E.; Wang, Xiang
Abstract: To elucidate the distribution and dispersion of RuO2 species on the reactivity, RuO2 −SnO2 catalysts with 2 % and 5 % Ru contents have been prepared with impregnation (IMP), deposition‐precipitation (DP) and co‐precipitation (CP) methods, and probed by CO oxidation. With IMP and DP methods, RuO2 crystallites are predominantly formed on the catalyst surface, which is favorable for CO oxidation. Moreover, the IMP catalyst possesses surface RuO2 having smaller mean crystallite size and better dispersion than the DP catalyst, thus SnRuO‐IMP displays higher activity than SnRuO‐DP at the same Ru loadings. However, with CP method, RuO2 species is mainly present as Ru 4+ cations in the lattice of rutile SnO2 to form a solid solution structure below the lattice capacity, which is less reactive than the surface RuO2 due to the restriction by the SnO2 lattice. In conclusion, surface RuO2 is revealed to be the active species, whose amount and dispersion determine the activity of the catalysts. By changing preparation methods, the distribution of RuO2 species in the catalysts is varied and impacts the reactivity of the catalysts evidently. The traditional impregnation is found to be the best method to prepare RuO2 −SnO2, which shows the highest activity among all the catalysts. Abstract : D&D control : A RuO2 −SnO2 catalyst with a larger amount of surface RuO2 that possesses a better dispersion has a higher activity.